Model Pendidikan Agama Kristen Moderasi Intra-Agama Berbasis Konsili Yerusalem dalam Kisah Para Rasul 15 - Yuwono, Stefanus Christianto; Agus Marulitua Marpaung (Sekolah Tinggi Teologi Real Batam, 2025)
Abstract: This article outlines a model of Christian Religious Education (CRE) that emphasizes the actual principle of intra-religious moderation, based on a case study of the Council of Jerusalem in Acts 15. The phenomenon of plurality necessitates an approach to religious moderation, both inter-religious and intra-religious. The Council of Jerusalem serves as a historical and theological guide for managing internal diversity within Christianity, resolving debates between Jewish and Gentile Christians regarding the implementation of circumcision and the Mosaic Law for salvation. Through historico-critical, exegetical, systematic-theological, and pedagogical analysis,this article identifies the principles of intra-religious moderation from the Council of Jerusalem: dialogue, respect for differences, focus on the essence of faith, agape love, communal consensus, and flexibility. These principles have pedagogical implications for CRE's content, methods, value inculcation, the role of teachers, and evaluation. This model offers opportunities to foster Christian tolerance, enrich the CRE curriculum, position the church as a peacemaker, and serve as a universal moderation model. Although facing challenges such as institutional resistance and educator competency, implementing this model is crucial for producing an inclusive and moderate Christian community. Abstrak: artikel ini menguraikan model Pendidikan Agama Kristen (PAK) yang menekankan prinsip aktual moderasi intra-agama, berlandaskan studi kasus Konsili Yerusalem dalam Kisah Para Rasul 15. Fenomena pluralitas menuntut pendekatan moderasi beragama, baik antar-agama maupun intra-agama. Konsili Yerusalem berfungsi sebagai panduan historis dan teologis untuk mengelola keragaman internal dalam Kristen, menyelesaikan perdebatan antara Kristen Yahudi dan non-Yahudi mengenai implementasi sunat dan hukum Taurat demi keselamatan.Melalui analisis historis-kritis, eksegetis, teologis-sistematis, dan pedagogis, artikel ini mengidentifikasi prinsip-prinsip moderasi intra-agama dari Konsili Yerusalem: dialog, penghormatan perbedaan, fokus esensi iman, kasih agape, konsensus bersama, serta fleksibilitas. Prinsip-prinsip ini berimplikasi pedagogis pada materi, metode, penanaman nilai, peran guru, dan evaluasi PAK. Model ini menawarkan peluang untuk membentuk toleransi Kristiani, memperkaya kurikulum PAK, menempatkan gereja sebagai pembawa damai, dan menjadi model moderasi universal. Walau menghadapi tantangan seperti resistensi institusi dan kompetensi pendidik, implementasi model ini krusial untuk menghasilkan umat Kristen yang inklusif dan moderat.